AKUNTANSI LINGKUNGAN DAN TRIPLE BOTTOM LINE ACCOUNTING: PARADIGMA BARU AKUNTANSI BERNILAI TAMBAH - I Wayan Suartana (Bumi Lestari Journal of Environment, 2010)
Every organization is an open system that has interaction and synergy with society and people. Most corporate or organization operate in a social, economic, technological, and political/social change brings both opportunities and threats. However, there is interdependence between business, regulation, and society in the need of a stable environment with an educated workforce. The corporate objective and principles is not only creating profit, but also that have impact on society and environment. Corporate and organization can implement the integration among economic, social and environmental aspect with social responsibility and triple bottom line accounting (TBLA). TBLA item is social accounting, ecological accounting, and economic accounting.